College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.5 - Factoring Polynomials - R.5 Exercises: 132

Answer

$6(x+5)^{3}(x-1)(x+1)$

Work Step by Step

We factor by grouping to obtain: $4(x+5)^{3}(x-1)^{2}+(x+5)^{4}* 2(x-1) =2(x+5)^{3}(x-1)[2(x-1)^1+(x+5)^1] =2(x+5)^{3}(x-1)(2x-2+x+5) =2(x+5)^{3}(x-1)(3x+3)\\ =2* 3(x+5)^{3}(x-1)(x+1) =6(x+5)^{3}(x-1)(x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.